The Binomial Parasite-Host Immunity in the Healing Process and in Reactivation of Human Tegumentary Leishmaniasis - Conceição-Silva, Fatima; Leite-Silva, Jessica; Morgado, Fernanda N. (Frontiers in Microbiology, 2018)
Leishmaniasis is a vector-borne infectious disease caused by different species of protozoa from the Leishmania genus. Classically, the disease can be classified into two main clinical forms: Visceral (VL) and Tegumentary (TL) leishmaniasis. TL is a skin/mucosal granulomatous disease that manifests mainly as cutaneous localized or disseminated ulcers, papules diffusely distributed, mucosal lesions or atypical lesions. Once the etiology of the infection is confirmed, treatment can take place, and different drugs can be administered. It has already been shown that, even when the scar is clinically evident, inflammation is still present in the native tissue, and the decrease of the inflammatory process occurs slowly during the first years after clinical healing. The maintenance of residual parasites in the scar tissue is also well documented. Therefore, it is no longer a surprise that, under some circumstances, therapeutic failure and/or lesion reactivation occurs. All over the years, an impressive amount of data on relapses, treatment resistance and lesion reactivation after healing has been collected, and several factors have been pointed out as having a role in the process. Different factors such as Leishmania species, parasite variability, Leishmania RNA virus 1, parasite load, parasite persistence, age, nutritional status, gender, co-morbidities, co-infection, pregnancy, immunosuppression, lesion duration, number and localization of lesions, drug metabolism, irregular treatment and individual host cellular immune response were described and discussed in the present review. Unfortunately, despite this amount of information, a conclusive understanding remains under construction. In addition, multifactorial influence cannot be discarded. In this context, knowing why leishmaniasis has been difficult to treat and control can help the development of new approaches, such as drugs and immunotherapy in order to improve healing maintenance. In this sense, we would like to highlight some of the findings that may influence the course of Leishmania infection and the therapeutic response, with an emphasis on TL.